O-GlcNAcylation: A New Cancer Hallmark? - Fardini, Yann; Dehennaut, Vanessa; Lefebvre, Tony; ISSAD, Tarik (Frontiers in Endocrinology, 2013)
O-linked N-acetylglucosaminylation (O-GlcNAcylation) is a reversible post-translational modification consisting in the addition of a sugar moiety to serine/threonine residues of cytosolic or nuclear proteins. Catalyzed by O-GlcNAc-transferase (OGT) and removed by O-GlcNAcase, this dynamic modification is dependent on environmental glucose concentration. O-GlcNAcylation regulates the activities of a wide panel of proteins involved in almost all aspects of cell biology. As a nutrient sensor, O-GlcNAcylation can relay the effects of excessive nutritional intake, an important cancer risk factor, on protein activities and cellular functions. Indeed, O-GlcNAcylation has been shown to play a significant role in cancer development through different mechanisms. O-GlcNAcylation and OGT levels are increased in different cancers (breast, prostate, colon…) and vary during cell cycle progression. Modulating their expression or activity can alter cancer cell proliferation and/or invasion. Interestingly, major oncogenic factors have been shown to be directly O-GlcNAcylated (p53, MYC, NFκB, β-catenin…). Furthermore, chromatin dynamics is modulated by O-GlcNAc. DNA methylation enzymes of the Tet family, involved epigenetic alterations associated with cancer, were recently found to interact with and target OGT to multi-molecular chromatin-remodeling complexes. Consistently, histones are subjected to O-GlcNAc modifications which regulate their function. Increasing number of evidences point out the central involvement of O-GlcNAcylation in tumorigenesis, justifying the attention received as a potential new approach for cancer treatment. However, comprehension of the underlying mechanism remains at its beginnings. Future challenge will be to address directly the role of O-GlcNAc-modified residues in oncogenic-related proteins to eventually propose novel strategies to alter cancer development and/or progression.